The involvement of hypoxia in APOBEC-mediated mutagenesis in multiple cancers - Liang, J (2018)
Mutational signatures have been studied to associate mutations to their originating causes. One such signature is that of the APOBEC family of proteins. APOBEC proteins are normally involved in innate immunity, playing a role in the defence against foreign genetic material by inducing mutations in single-stranded DNA and RNA. APOBECs have recently been associated to mutations in the genomes of multiple human cancers. The regulation of APOBEC genes is currently poorly understood, especially in the context of cancer. Recent evidence suggests that certain APOBEC genes can be upregulated in immune cells exposed to hypoxia. I explore this path further by studying the association between hypoxia and APOBEC expression and activity in cancer using RNA-Seq, mutation, and amplification data from 6723 patients in 13 cancer types. My results show evidence of correlation between hypoxia and APOBEC gene expression as well as mutagenic activity, specifically APOBEC3A and 3B. I also show that APOBEC3B is involved in pathways that overlap with those associated with hypoxia, contrary to the other APOBEC family members. Finally, I provide a comparison of the methods used to evaluate the APOBEC mutational signature. Overall, this study provides preliminary evidence for the association between APOBEC and hypoxia. It also raises many questions, but it provides solid grounds for future studies to be conducted in more depth about this topic.